An introduction to banking : principles, strategy and risk management - Choudhry, Moorad (John Wiley & Sons, Inc., 2017)
Introduction to Banking, Second Edition is a comprehensive and jargon-free guide to the banking operation. Written at the foundational level, this book provides a broad overview of banking to give you an all-around understanding that allows you to put your specialty work into context within the larger picture of your organization. With a specific focus on risk components, this second edition covers all key elements with new chapters on reputational risk, credit risk, stress testing and customer service, including an updated chapter on sustainability. Practical material includes important topics such as the yield curve, trading and hedging, asset liability management, loan origination, product marketing, reputational risk and regulatory capital.--